2D and 3D Nanopatterning of Titanium for Enhancing Osteoinduction of Stem Cells at Implant Surfaces. Issue 9 (12th March 2013) - Sjöström, Terje; McNamara, Laura E.; Meek, R. M. Dominic; Dalby, Matthew J.; Su, Bo
Abstract The potential for the use of well‐defined nanopatterns to control stem cell behaviour on surfaces has been well documented on polymeric substrates. In terms of translation to orthopaedic applications, there is a need to develop nanopatterning techniques for clinically relevant surfaces, such as the load‐bearing material titanium (Ti). In this work, a novel nanopatterning method for Ti surfaces is demonstrated, using anodisation in combination with PS‐b‐P4VP block copolymer templates. The block copolymer templates allows for fabrication of titania nanodot patterns with precisely controlled dimensions and positioning which means that this technique can be used as a lithography‐like patterning method of bulk Ti surfaces on both flat 2D and complex shaped 3D surfaces. In vitro studies demonstrate that precise tuning of the height of titania nanodot patterns can modulate the osteogenic differentiation of mesenchymal stem cells. Cells on both the 8 nm and 15 nm patterned surfaces showed a trend towards a greater number of the large, super‐mature osteogenic focal adhesions than on the control polished Ti surface, but the osteogenic effect was more pronounced on the 15 nm substrate. Cells on this surface had the longest adhesions of all and produced larger osteocalcin deposits. The results suggest that nanopatterning of Ti using the technique of anodisation through a block copolymer template could provide a novel way to enhance osteoinductivity on Ti surfaces.